Li‐Ion Batteries: Exploring Lithium Deficiency in Layered Oxide Cathode for Li‐Ion Battery (Adv. Sustainable Syst. 7/2017). (July 2017) - Cho, Sung‐Jin; Uddin, Md‐Jamal; Alaboina, Pankaj K.; Han, Sang Sub; Nandasiri, Manjula I.; Choi, Yong Seok; Hu, Enyuan; Nam, Kyung‐Wan; Schwarz, Ashleigh M.; Nune, Satish K.; Cho, Jong Soo; Oh, Kyu Hwan; et al.
Abstract : While futuristic‐all‐electric cars are set to revolutionize the clean energy concept, it is the time to consider the sustainability of the lithium sources. Article number1700026, by Sung‐Jin Cho and co‐workers, features the lithium deficient ratio, as opposed to the general trend of lithium excess ratio, and provides a new perspective on energy storage sustainability.